KV1 and KV3 Potassium Channels Identified at Presynaptic Terminals of the Corticostriatal Synapses in Rat - David Meneses; Ana V. Vega; Francisco Miguel Torres-Cruz; Jaime Barral (Neural Plasticity)
In the last years it has been increasingly clear that KV-channel activity modulates neurotransmitter release. The subcellular localization and composition of potassium channels are crucial to understanding its influence on neurotransmitter release. To investigate the role of KV in corticostriatal synapses modulation, we combined extracellular recording of population-spike and pharmacological blockage with specific and nonspecific blockers to identify several families of KV channels. We induced paired-pulse facilitation (PPF) and studied the changes in paired-pulse ratio (PPR) before and after the addition of specific KV blockers to determine whether particular KV subtypes were located pre- or postsynaptically. Initially, the presence of KV channels was tested by exposing brain slices to tetraethylammonium or 4-aminopyridine; in both cases we observed a decrease in PPR that was dose dependent. Further experiments with tityustoxin, margatoxin, hongotoxin, agitoxin, dendrotoxin, and BDS-I toxins all rendered a reduction in PPR. In contrast heteropodatoxin and phrixotoxin had no effect. Our results reveal that corticostriatal presynaptic KV channels have a complex stoichiometry, including heterologous combinations KV1.1, KV1.2, KV1.3, and KV1.6 isoforms, as well as KV3.4, but not KV4 channels. The variety of KV channels offers a wide spectrum of possibilities to regulate neurotransmitter release, providing fine-tuning mechanisms to modulate synaptic strength.